Computational dosimetry and post-irradiation studies of the electron beam irradiation-assisted corrosion and stress corrosion cracking of statically strained steel samples in a supercritical water coolant - Bakai, O.S.; Boriskin, V.M.; Bratchenko, M.I.; Dyuldya, S.V. (Вопросы атомной науки и техники, 2022)
New experimental data on the corrosion behavior of the 12X18H10T austenitic steel elastically strained cou-pons after 500 h long exposure in situ the NSC KIPT “Electron Irradiation Test Facility” supercritical water circulation loop are presented and discussed. The γ-activation analysis based computational dosimetry of samples is correlated to their weight gain/loss measurement data. The absorbed dose and stress effect on their irradiation assisted general corrosion is revealed. The corrosion surface/layer chemistry/microstructure are discussed with special emphasis of the irradiation/stress impact on the protective coating stability, intergranular corrosion and precursors of cracking.